Production of SO2 Binding Compounds and SO2 by Saccharomyces during Alcoholic Fermentation and the Impact on Malolactic Fermentation - Wells, A.; Osborne, J.P. (South African Journal of Enology and Viticulture, 2011)
The objective of this study was to investigate the production of SO2 and SO2 binding compounds by wine yeast and the impact of the production of these compounds on the MLF at various time points during alcoholic fermentation. Fermentations were observed for a number of commercial wine yeasts in a synthetic grape juice and Pinot gris juice and SO2, acetaldehyde, pyruvic acid and α-ketoglutarate. Measurements were taken at multiple time points during the fermentation. Samples were taken from the fermentations at weekly intervals, sterile filtered, and inoculated with O. oeni strain VFO to induce MLF. Significant differences between the amount of SO2, acetaldehyde and pyruvic acid produced by the various yeast strains were noted. Some yeast strains such as FX10, CK S102, F15 and M69, produced significantly higher SO2 concentrations than other yeast strains and MLF was inhibited in these wines. Insignificant free SO2 was measured, indicating that bound SO2 rather than free SO2 was responsible for inhibition. At almost all time points of the alcoholic fermentation, acetaldehyde bound SO2 was determined to be the dominant species of bound SO2 present, suggesting that MLF inhibition by bound SO2 was due to acetaldehyde bound SO2.